Fabrication and electrical characterization of homo- and hetero-structure Si/SiGe nanowire Tunnel Field Effect Transistor grown by vapor–liquid–solid mechanism. (April 2016) - Brouzet, V.; Salem, B.; Periwal, P.; Alcotte, R.; Chouchane, F.; Bassani, F.; Baron, T.; Ghibaudo, G.
Highlights: Ω-gate TFETs based on p-Si/i-Si/n + -Si0.7 Ge0.3 NWs heterostructure grown by CVD–VLS. Ge insertion allows improving the electrical performances of TFET. The Si/SiGe TFET presents a better electrical performance than the Si TFET device. The B2BT model's parameters have been extracted for the Si0.7 Ge0.3 nanowires. Abstract: We demonstrate the fabrication and electrical characterization of Ω -gate Tunnel Field Effect Transistors (TFET) based on p-Si/i-Si/n + Si0.7 Ge0.3 heterostructure nanowires grown by Chemical Vapor Deposition (CVD) using the vapor–liquid–solid (VLS) mechanism. The electrical performances of the p-Si/i-Si/n + Si0.7 Ge0.3 heterostructure TFET device are presented and compared to Si and Si0.7 Ge0.3 homostructure nanowire TFETs. We observe an improvement of the electrical performances of TFET with p-Si/i-Si/n + Si0.7 Ge0.3 heterostructure nanowire (HT NW). The optimized devices present an Ion current of about 245 nA at V DS  = −0.5 V and V GS  = −3 V with a subthreshold swing around 135 mV/dec. Finally, we show that the electrical results are in good agreement with numerical simulation using Kane's Band-to-Band Tunneling model.